Evaluation of Oxidant-Antioxidant Imbalance, Level of Nitrite, and Level of Catalase as Biomarker in Plasma Samples of Chronic Obstructive Pulmonary Disease (COPD) Patients - Kalra, Pratibha (My University, 2023)
This dissertation aims to investigate potential biomarkers for Chronic Obstructive Pulmonary Disease (COPD) sensitivity, focusing on oxidative stress and antioxidant capacity. Three specific biomarkers were evaluated: Total Antioxidant Capacity (TAC) measured through 2,2- Diphenyl-1-picrylhydrazyl (DPPH) and Ferric Reducing Antioxidant Power (FRAP) assays, Nitrite levels using the Griess assay, and Catalase activity through Catalase In-Gel Activity Assay. The study enrolled 160 participants, including COPD patients and healthy controls. The DPPH assay revealed no statistically significant difference in TAC between COPD patients (mean 10.12 ± 0.04 μg/ml) and healthy controls (mean 11.03 ± 0.02 μg/ml). Additionally, TAC did not significantly differ among COPD patients based on age, gender, smoking status, and COPD severity. The FRAP assay, however, indicated a significantly higher TAC in COPD patients (mean 57.02 ± 0.27 μg/ml) compared to healthy controls (mean 23.43 ± 0.22 μg/ml). Furthermore, the Griess assay demonstrated a lower concentration of nitrites in the plasma of COPD patients compared to healthy controls. While no significant differences in nitrite levels were observed among different subgroups of COPD patients based on age, smoking status, COPD severity, and symptoms (CAT scores), the findings suggest an alteration in the nitric oxide pathway in COPD. The Catalase In-Gel Activity Assay revealed lower catalase activity in COPD patients compared to healthy controls. This finding implicates a potential link between reduced catalase activity and increased oxidative stress in COPD patients, contributing to disease pathogenesis. The study's implications suggest the importance of exploring oxidative stress and antioxidant capacity in COPD management. Identifying reliable biomarkers for COPD sensitivity can aid in disease diagnosis and personalized treatment approaches. However, the study has certain limitations, including the cross-sectional design, small sample size, and potential confounding factors like diet and lifestyle choices. In conclusion, this dissertation provides valuable insights into potential biomarkers for COPD sensitivity related to oxidative stress and antioxidant capacity. The results shed light on the complexity of antioxidant status in COPD, warranting further research with larger cohorts and comprehensive assessments. Exploring the impact of specific antioxidant interventions and conducting longitudinal studies can enhance understanding and contribute to novel therapeutic strategies for COPD management.
Keywords: copd; catalase; nitrate; FRAP